Lactation Education by Midwives in Supporting Exclusive Breastfeeding - Yunri Merida; Retno Wulan (PT Bukuloka Literasi Bangsa, 2025)
Exclusive breastfeeding for the first six months of life is an important intervention in improving infant health and nutritional resilience, but the success rate in Indonesia has not yet reached the national target. The urgency of this study lies in the importance of understanding the role of midwives in providing lactation education as an effective strategy to improve exclusive breastfeeding practices. This study aims to analyze how lactation education provided by midwives contributes to improving mothers' knowledge, attitudes, and behaviors regarding breastfeeding. The study uses a qualitative approach with a literature review method, examining five relevant national scientific publications on the topic of lactation education and exclusive breastfeeding practices. The data were analyzed thematically by identifying patterns, concepts, and relationships between research results. The results of the analysis show that lactation education by midwives has a significant impact on increasing mothers' knowledge, forming positive attitudes towards breastfeeding, and strengthening emotional and social support for mothers. In addition, continuous training for midwives has been proven to increase the competence and effectiveness of the education provided. These findings contribute to the strengthening of health behavior theory and midwifery practices based on maternal empowerment. This study concludes that the success of exclusive breastfeeding requires a holistic, innovative, and sustainable educational approach. It is recommended that future research use a triangulation approach and expand the sociocultural context to enrich the understanding of the phenomenon of lactation education in Indonesia. Keywords: lactation education, midwifery personnel, exclusive breastfeeding, maternal and child health, breastfeeding promotion.